FEMALE GENITAL TUBERCULOSIS, A 10 YEAR CLINICO-PATHOLOGIC STUDY - W. Karimi; H. Emami (Tehran University of Medical Sciences, 1975)
The results of 10 year clinico - pathologic study about female genital tuberculosis in Isfahan are reported. The main aims of this investigation were to study and review the tuberculosis of female genital tract to evaluate the influence of treatment and above all, to attempt to gain a better insight into the relation of infertility to this disease. In this study the following points have been taken into consideration: age incidence, previous health, presence of absence of other forms of tuberculosis, principle symptoms, bacteriologic and histological findings, the frequency of unsuspected endometrial tuberculosis, cases treated medically and surgically, and conception rate following treatment. The diagnostic procedures used in detection of these cases included: endometrial curettage biopsy, bacteriologic and histopathology examination of tissues removed from female genital organs, and laparotomy.